WATER-IN-OIL EMULSION COMPOSITIONS AND METHODS FOR MAKING AND USING THE SAME - DAVIS, Matthew J; CHEN, Haunn-Lin, (Tony); LEWELLYN, Morris; CYWAR, Douglas A (2018)
The suspended solids content of a process stream in a process for producing alumina is reduced by contacting the stream with silicon-containing polymers provided by water-in-oil compositions.